Exploring the quality of mohair fiber produced and auctioned in Argentina by Angora goat farmer organizations - Sacchero, Diego Mariano (2025)
Mohair fiber production faces various challenges, such as those related to production environments, sustainability, the supply chain and consumer demands. In Argentina, mohair is produced in Patagonia, in mixed and extensive livestock fiber-meat systems, and exported in combed, washed or raw state. This study analyzed data on mohair fiber quality within the Mohair Program, a national public policy, aiming to provide insights to monitor and address current and future challenges in the mohair fiber industry. The data analyzed included annual records of 612 commercial samples from 24 collection centers from 2014 to 2023. The variables analyzed were mean fiber diameter (MFD), percentages of non-objectionable medullated fibers (NOB) and Kemp-type medullated fibers (KMP), yield (YLD) and vegetal matter (VEG). The MFD overall trend showed a positive slope, indicating an increase from 27.3 to 28.8 μm over time. In Argentina, MFD is finer than in South Africa, suggesting potential for increased production via nutrition and genetics. The general trend for NOB fibers indicated a slight decrease over time. Comparison of NOB fibers at the beginning and at the end of the time series showed a decrease from 2.45 % to 1.75 %. On the other hand, KMP fibers increased during the period analyzed, exceeding 1 % in 2018 and slightly 2.0 % in the last shearing season. Reducing KMP values represents the largest pending task within the Mohair Program. The YLD values were high (83.0–87.2 %) and VEG values very low (<1 %), contributing to the excellent quality parameters of Argentine mohair.